TI_GERICHTE 12.2009.174 vom 23. April 2012 , Contratto - interpretazione - donazione - responsabilità del padrone d'azienda - TI Tribunale d'appello (2012)
Contratto - interpretazione - donazione - responsabilità del padrone d'azienda